Socio-emotional learning skills and teaching practices of teachers and educators - Mercedes A. Macarandang; Ethel de Leon-Abao; Maria Elena C. Morales; Nelia G. Prieto; Filomena T. Dayagbil; Rivika C. Alda (Institute of Advanced Engineering and Science, 2026)
The COVID-19 pandemic reshaped the global educational system, mandating teachers to adapt to new modes of instruction. This shift heightened the importance of socio-emotional learning (SEL) in fostering effective teaching and learning. This study examined the socio-emotional skills of teachers and their instructional practices. A descriptive correlational design was employed, with data collected through a purposive sampling procedure. A total of 1,211 teachers from basic and higher education institutions across the Philippines were selected through stratified random sampling. Correlation analysis revealed a significant positive relationship between teachers’ socio-emotional competencies, particularly self-awareness and relationship skills, and their instructional practices. These findings highlight the need to integrate SEL into professional development initiatives. It is recommended that a competency-based training framework be developed to strengthen teachers’ socio-emotional capacities, ensuring they are well-equipped to meet the demands of post-pandemic education.